Designing Student’s Registration Book and Student’s Report Card Processing Application For Pangudi Luhur Don Bosko Elementary School Semarang - Adrianus Hermawan Susanto; Erdhi Widyarto; Bernardinus Harnadi (Soegijapranata Catholic University, 2020)
The development of information and communication technology continues to run over time in various fields, without exception in the field of education. Master data management of students has now started using electronic media. At Pangudi Luhur Don Bosko Elementary School also used electronic media in its management, but the application has limitations in storing data, therefore the authors designed the